Teacher Experience of Integrating Tablets in One-to-One Environments: Implications for Orchestrating Learning - Hye Jeong Kim; Jiyoung Choi; Suyoun Lee (MDPI AG, 2019)
We investigated teachers’ perceptions and behaviors regarding the integration of tablets into their activities in the one-to-one classroom. The use of tablets in classroom instruction can enrich the pedagogical quality of students’ collaborative activities, enhance classroom engagement, and facilitate various classroom activities. Seven focus group interviews were conducted with 37 teachers from seven rural public schools in Korea. Data were mostly generated using semi-structured interviews and were then analyzed using content analysis. Our results show that teachers made efforts to incorporate various interactive activities into the classroom using tablets. With technology tailored to one-to-one environments, interactive instruction was based on teachers’ perceptions of the unique advantages of the tablets and relevant technologies. The teachers reported that instruction using one-to-one technology could enhance each student’s engagement. However, the teachers faced multiple challenges in using tablets in terms of meeting their instructional objectives or teaching goals in the context of classroom teaching. In tablet-integrated classes, the teachers reported curriculum completion issues and the need for a longer period of teacher training before tablet integration. This study is valuable because few studies discuss the role of teachers with regard to their pedagogical experiences with tablet-integrated classrooms in the context of one-to-one computing activities.